Tuning biological nutrient removal plants - Hartley, Ken (IWA Publishing, 2013)
Tuning BNR Plants increases interest in tuning to enhance both performance and capacity, to provide insight into typical plant operating characteristics, and to stimulate operators' interest in studying the behaviour of their own plants.